Business strategy formulation of eggshell party planner to face competitive environment - Mirah Tiara, Sheila; Toha, Mohamad (The Indonesian Journal of Business Administration, 2016)
Abstract. Eggshell Party Planner is a company operates in wedding decorations since 2013. The company is still growing however it faces (1) Many competitors are entering the same segment in the décor service industry, however, the market has limitation, Eggshell Party Planner in the near future will find difficulties, (2) Sales of Decoration service is around 95% of total sales. It means that Eggshell Party Planner still very weak in other product, (3) If Eggshell Party Planner just playing for wedding decoration, the increasing number of competitors and their innovation threaten the position of Eggshell Party Planner, (4) Vendors or partners who cooperate with Eggshell Party Planner began to steal the company’s market. They learn how Eggshell Party Planner work then practice using the same practices like Eggshell Party Planner do. They are also trying to imitate Eggshell Party Planner’s product. Steps taken to solves the problem are (1) Internal analysis (business models canvas, VRIO framework, Resource Based View), (2) external analysis (PEST analysis, industry analysis, competitor analysis), (3) SWOT, (4) The Strategy Diamond, (5) strategies to avoid imitation products, (6) strategy to conduct partnership. The method used in this research are quantitative and qualitative research. The Qualitative research were conducted interviews to 10 people who are preparing for the wedding, and the quantitative distributed to 106 respondents by Eggshell Party Planner’s customer in Jakarta and Central Java.The results of this final project are (1) Strategies to win the competition, Eggshell Party Planner using diamond strategy, With the limitations of the market Eggshell Party Planner will focus to customers, concern about the service, Time, creativity, portfolio, price. as the target of their segments, based on the SWOT analysis, (2) There are 5 Variables key success factors, based on the level of performance, (3) There are several steps to perform the activities of the most important. priorities derived from the benefits of the activity and also Eggshell Party Planner capability in terms of resources (4) Eggshell Party Planner estimate their sales in year 2. their sales will increase, from IDR 336.960.000 to IDR 374.400.000. This will increase to 10% and will continue to increase every year, (5) And vehicles that will be used by Eggshell Party Planner is an activity that is done on the staging, (6) The unique concept of graphic design, flexible prices, market niche, Innovation constantly, Strong Brand, service great. With this steps, Eggshell Party Planner will be able to avoid the imitation by partner or competitor, (7) Partnership strategy should be applying for Eggshell Party Planner is a cross-media promotion or strategic alliances for the win from competitors. Based on the result, Eggshell Party Planner is recommended to (1) Eggshell Party Planner should focus in the selecting market segment that concern about service, Time, creativity, portfolio, price. (2) Diamond Strategy is effective strategy to win the competition, (3) Eggshell Party Planner must have The unique concept of graphic design to avoid the imitation, and Eggshell Party Planner must add a graphic designer for continuing the innovation from company. (4) Eggshell Party Planner should be partner with vendors that support the industry of Eggshell Party Planner for the win from competitors. Keywords: Diamond Strategy, Wedding Decoration, Partnership Strategy, Business Model Canvas